Genetic Association between Xeroderma Pigmentosum Polymorphism Rs2228000 with Staging and Development of Bladder Cancer - Saleh Ali Al-Qadoori (Journal of Global Pharma Technology, 2018)
Background: Bladder Cancer is the sixth most common malignancy in males worldwide, and the second in Iraq. XPC Repair Gene polymorphism may cause a reduction in DNA repair capacity and inﬂuence an individual’s susceptibility to bladder cancer and the prognosis of the disease. Objective: To investigate the influence of active tobacco smoking on human DNA repair gene XPC rs2228000 polymorphism in patients with bladder cancer and the impact of XPC polymorphism C>T to the staging and development of the disease. Methods: A total of 62 of histo-pathologically confirmed diagnosed bladder cancer patients, and 38 age-matched healthy controls were involved in the study. All were recruited from February to September 2017 in a case-control study conducted in the Department of Biochemistry at the College of Medicine University of Baghdad. Genotyping of the XPC rs2228000 (C>T) was evaluated using a polymerase chain reaction and by Sanger sequencing method. The odds ratio (OR) and 95% confidence interval (CI) were calculated as a measure of the combined effect of cigarette smoking, and DNA Double-Strand breaks Repair Gene XPC Polymorphism on bladder cancer risk, staging, and development.  Result: Heterozygous genotype of the XPC rs2228000 (C>T) showed a significant increase in bladder cancer risk OR (95% CI) = 2.75 (1.0-7.2), p value<0.05. Also, the study found that patients with the polymorphic allele (T genotype) have significantly increased the risk of bladder cancer (OR, 2.7; *p = 0.02). A statistically highly significant increased bladder cancer risk in the smoker with T Allele (OR, 4.3; **p = 0.004). Moreover, T Allele genotypes were also observed to be associated with a significantly increased risk of T1 (OR, 3.9; **p = 0.005). Conclusion: The study suggests that having polymorphic gene genotype of DNA Repair Gene XPC rs2228000 could increase the risk of bladder cancer and also affect the development and staging of the disease while having the genotype could decrease the risk of bladder cancer and increase the survival rate of bladder cancer patients.Keywords: Bladder Cancer, XPC, Rs2228000, Polymorphism.